Joint effect of ferromagnetic and non-ferromagnetic cations for adjusting room temperature ferromagnetism of highly luminescent CuNiInS quaternary nanocrystals. (8th December 2016) - Shen, Jin; Wang, Chunlei; Xu, Shuhong; Lv, Changgui; Zhang, Ruohu; Cui, Yiping
Abstract: In this work, highly luminescent quaternary CuNiInS nanocrystals (NCs) are put forward as a good prototype for investigating defect-induced room temperature ferromagnetism. A ferromagnetic Ni cation can preserve the strong luminescence of NCs without introducing intermediate energy levels in the center of the forbidden band. The strong luminescence of NCs is used as an indicator for monitoring the concentration of vacancy defects inside them, facilitating the investigation of the origin of room temperature ferromagnetism in CuNiInS NCs. Our results reveal that the patching of Cu vacancies ( V Cu − ) with Ni will result in bound magnetic polarons composed of both V Cu − and a substitution of Cu by Ni ( Ni Cu + ), giving rise to the room temperature ferromagnetism of CuNiInS NCs. Either the ferromagnetic Ni or the non-ferromagnetic Cu cation can tune the magnetism of CuNiInS NCs because of the change of bound magnetic polaron concentration at the altered concentration ratio of V Cu − and Ni Cu + .